2012
DOI: 10.7883/yoken.65.264
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern and the Indicator of Decreased Ciprofloxacin Susceptibility of Salmonella enterica Serovar Typhi Isolated from Dhulikhel Hospital, Nepal

Abstract: SUMMARY:Monitoring the antibiotic susceptibility pattern of Salmonella enterica serovar Typhi (S. Typhi) is important for efficiently managing cases of typhoid fever. In this study, the antimicrobial susceptibility patterns of 114 S. Typhi isolates, which were collected from a university hospital in Nepal during July 2009-December 2010, were investigated by disc diffusion assays. All of the S. Typhi isolates were sensitive to amoxycillin-clavulanic acid. More than 95z of the isolates were sensitive to chloramp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
(19 reference statements)
6
16
1
Order By: Relevance
“…14 In 2003, the World Health Organization published guidelines that recommended azithromycin, ceftriaxone, or cefixime for quinolone-resistant Salmonella typhi and paratyphi A infections. 15 Our studies showed ceftriaxone, cefotaxime and cefixime had a sensitivity of 100%, which on the contrary, with the study done at the Dhulikhel hospital by Dhurba et al 13 in 2012, where ceftriaxone was 96.6% and cefotaxime was 87.8% sensitive. Similarly, a study done by Dahiya et al 16 showed third-generation cephalosporins were 100% sensitive to Salmonella typhi and paratyphi A.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…14 In 2003, the World Health Organization published guidelines that recommended azithromycin, ceftriaxone, or cefixime for quinolone-resistant Salmonella typhi and paratyphi A infections. 15 Our studies showed ceftriaxone, cefotaxime and cefixime had a sensitivity of 100%, which on the contrary, with the study done at the Dhulikhel hospital by Dhurba et al 13 in 2012, where ceftriaxone was 96.6% and cefotaxime was 87.8% sensitive. Similarly, a study done by Dahiya et al 16 showed third-generation cephalosporins were 100% sensitive to Salmonella typhi and paratyphi A.…”
Section: Discussioncontrasting
confidence: 52%
“…12 Resistance to ciprofloxacin is now being reported both from the Indian subcontinent and the West. 6 Our study showed ciprofloxacin was resistant in 44.7% cases and intermediately sensitive in 49.1% patients, but the study done by Dhurba et al 13 in 2012 showed both ofloxacin and ciprofloxacin were resistant in only 1.8% each and intermediately sensitive in 7% and 18.4% of patients respectively. Compared to other quinolones, namely ciprofloxacin and levofloxacin, the ofloxacin showed 100% sensitivity in our study, which is almost similar to the another study with 98.2% sensitivity.…”
Section: Discussionmentioning
confidence: 52%
“…Salmonella spp is the most common isolate indicating that enteric fever is endemic in various parts of Nepal. 2,4,5,15 All the cases of enteric fever were community acquired. An experiment on 112 cases of typhoid fever in out-patients at Dhulikhel Hospital in 2004 showed a higher percentage of infection in males than in females with a ratio of 3:1.…”
Section: Discussionmentioning
confidence: 99%
“…17 In recent years many case studies has shown failure in the treatment of enteric fever with isolates susceptible to fl uoroquinolones and resistant to Nalidixic acid. 2,18 Hence routine testing of resistance to Nalidixic acid can serve as a useful screening test for fl uoroquinolones. 18 The increase in the resistivity of the antibiotics like Ciprofl oxacin from 0 % in 2005 to 33.33 % in 2013 might have occurred due to the long-term use of the drugs or the misuse of the drugs by the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation